A calibrated weakest-link model for probabilistic assessment of LCF life considering notch size effects. (August 2020) - Liu, Xi; Wang, Rongqiao; Hu, Dianyin; Mao, Jianxing
Graphical abstract: We develop a calibrated weakest-link model for probabilistic assessment of LCF life considering the influence of the geometric size effect and the statistical size effect. Model parameters are estimated and calibrated based on the experimental data. Highlights: Calibrated weakest-link model is developed based on damage parameter in low cycle fatigue regime. Geometric and statistical size effects during crack initiation and propagation are explored. Bayesian inference method is applied for calibrating Weibull parameters. Deterministic and probabilistic LCF life are predicted for CHP specimens with different scales. Abstract: This study proposes a calibrated weakest-link model for probabilistic life in low cycle fatigue (LCF) regime considering the geometric size effect and the statistical size effect. Weakest-link model is first extended to LCF regime by using damage parameter, and then calibrated based on crack propagation process. Meanwhile, experiments on standard smooth specimens and central hole plate (CHP) specimens are conducted. To improve model accuracy, parameters in the proposed model are calibrated by using Bayesian inference method. Finally, probabilistic LCF life is predicted for CHP specimens with different scales, which shows good agreement with test data.